Fire in the belly: A scoping review of the immunopathological mechanisms of acute pancreatitis - Karthik Venkatesh; Karthik Venkatesh; Hannah Glenn; Anthony Delaney; Anthony Delaney; Christopher R. Andersen; Christopher R. Andersen; Christopher R. Andersen; Sarah C. Sasson; Sarah C. Sasson (Frontiers in Immunology, 2023)
IntroductionAcute pancreatitis (AP) is characterised by an inflammatory response that in its most severe form can cause a systemic dysregulated immune response and progression to acute multi-organ dysfunction. The pathobiology of the disease is unclear and as a result no targeted, disease-modifying therapies exist. We performed a scoping review of data pertaining to the human immunology of AP to summarise the current field and to identify future research opportunities.MethodsA scoping review of all clinical studies of AP immunology was performed across multiple databases. Studies were included if they were human studies of AP with an immunological outcome or intervention.Results205 studies met the inclusion criteria for the review. Severe AP is characterised by significant immune dysregulation compared to the milder form of the disease. Broadly, this immune dysfunction was categorised into: innate immune responses (including profound release of damage-associated molecular patterns and heightened activity of pattern recognition receptors), cytokine profile dysregulation (particularly IL-1, 6, 10 and TNF-α), lymphocyte abnormalities, paradoxical immunosuppression (including HLA-DR suppression and increased co-inhibitory molecule expression), and failure of the intestinal barrier function. Studies including interventions were also included. Several limitations in the existing literature have been identified; consolidation and consistency across studies is required if progress is to be made in our understanding of this disease.ConclusionsAP, particularly the more severe spectrum of the disease, is characterised by a multifaceted immune response that drives tissue injury and contributes to the associated morbidity and mortality. Significant work is required to develop our understanding of the immunopathology of this disease if disease-modifying therapies are to be established.